Creación de una empresa manufacturera y exportadora de cinturones de cuero, en la ciudad de santa marta. (2023)
"Our project, named ARSENATE, focuses on the export of high-quality leather belts from Colombia to the German market, this initiative represents a strategic opportunity in an interconnected and promising world, through a thorough market study, we have identified the preferences and trends of the German consumer, supporting our decision to enter this market with significant growth potential. The project is not limited to marketing; it also encompasses the creation of a strong organizational structure, efficient production processes, compliance with international regulations, and a solid financial plan, these elements ensure smooth trade and sustainable growth in the export of leather belts, our goal is to have a positive impact on both the Colombian leather industry and the local economy by offering high-quality products and maintaining a commitment to sustainability."